Pengelolaan Arsip Menggunakan Procurement Activity and Progress Information di Unit Procurement Proyek Indarung VI PT Semen Padang - Aditio, Bambang; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
This paper discussed about records management system in the Procurement Unit of Project Indarung VI of PT Semen Padang. This paper aims to: (1) describe the records management in the Procurement Unit; (2) describe the utilization implementation Procurement Activity and Progress Information in the records management; (3) describe the efforts made to overcome the constraints of the application utilization Procurement Activity and Progress Information in records management. Based on data analysis can be concluded that the management of the archive in the Procurement Unitis still not in accordance with the provisions and rules of good records management. It can be seen from the various obstacles encountered in records management and retrieval of archives as well as the constraints experienced by users in records management using the application Procurement Activity and Progress Information like error and not maximum features available in this application. Archive management in this unit is also more emphasis on the management is electronic compared to manually archive management, management of this kind makes the archive to be neglected. To overcome the problem that occurred in the management of problem-solving efforts should be made to be formulated together.Keywords : Record Management, Procurement Unit